1968
DOI: 10.2307/1936533
|View full text |Cite
|
Sign up to set email alerts
|

Some Niche Differences in Three Lesser Antillean Lizards of the Genus Anolis

Abstract: This paper documents interspecific and intraspecific differences in certain niche parameters among 3 species of lizards of the genus Anolis occurring in the southern Lesser Antilles. The 2 species whose ranges broadly overlap in Grenada show significant differences in body temperatures and food size distributions. Although there is considerable difference in the maximum size attained by the 2 species, animals with identical head and body lengths have radically contrasting distributions of prey size: smaller in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
166
4
2

Year Published

1970
1970
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(180 citation statements)
references
References 15 publications
8
166
4
2
Order By: Relevance
“…If there is sexual dimorphism in size, the match between lizard and perch may reduce intraspecific competition by habitat partitioning (COLLETTE 1961, SCHOENER 1968, WILLIAMS 1983, LOSOS 1990). However, the sexual dimorphism in size observed for G. humeralis in this study was less pronounced than that observed for Anolis species, from which habitat partitioning related to the match between lizard size and perch diameter has been repeatedly reported (SCHOENER 1968, SCHOENER & GORMAN 1968, HUEY et al 1983. Moreover, many studies have demonstrated that in areas with marked rainfall seasonality, arthropods are more abundant during the rainy season (e.g., BALLINGER & BALLINGER 1979, GRIFFITHS & CHRISTIAN 1996 which may reflect a higher abundance of resources.…”
Section: Discussioncontrasting
confidence: 44%
“…If there is sexual dimorphism in size, the match between lizard and perch may reduce intraspecific competition by habitat partitioning (COLLETTE 1961, SCHOENER 1968, WILLIAMS 1983, LOSOS 1990). However, the sexual dimorphism in size observed for G. humeralis in this study was less pronounced than that observed for Anolis species, from which habitat partitioning related to the match between lizard size and perch diameter has been repeatedly reported (SCHOENER 1968, SCHOENER & GORMAN 1968, HUEY et al 1983. Moreover, many studies have demonstrated that in areas with marked rainfall seasonality, arthropods are more abundant during the rainy season (e.g., BALLINGER & BALLINGER 1979, GRIFFITHS & CHRISTIAN 1996 which may reflect a higher abundance of resources.…”
Section: Discussioncontrasting
confidence: 44%
“…Insolation preferences of the two species contrast throughout Grenada. In the same species, the larger the head and body size, the larger the average prey size and proportion of large prey (for an elaboration see Schoener and Gorman 1968). Despite highly significant statistical differences between the prey size distribu-1 Received February 7, 1969;accepted October 9, 1%9. tions of the two species, common utilization of certain prey sizes was considerable.…”
mentioning
confidence: 99%
“…1, that the inclination of the regression line was significant (p < 0.05), the progression of the line occurred within Dyar's constant. The diferential growth from one instar to the other suggests to us that this occurs due to the superposition of niches, for, the fewer the larval instars, the greater will be the competition for food items of a given dimension studies in bird populations (MacArthur, 1958;Orians & Horn, 1969;MacArthur, 1971;Cody, 1974;Diamond, 1975;Hespenheide, 1975), in rodent populations (Brown, 1975;Rosenzweig et al, 1975;Mares & Williams, 1977), in lizard populations (Schoener & Gorman, 1968;Pianka, 1973;Schoener, 1975) and in fish populations (Zaret & Rand, 1971;Roughgarden, 1974;Werner, 1977), have suggested that competition exerts a major part regarding structure and function within the communities. These studies have shown that that the differential utilization of micro-habitat and food (size and/or taxons) were the factors that most influenced the minimization of competition and yet contributing to establish coexistence.…”
Section: Resultsmentioning
confidence: 99%